2005
DOI: 10.1021/la0504356
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Gold Nanoparticle Composite Nanostructures Using Thermosensitive Core−Shell Particles as a Template

Abstract: We report the formation of novel thermosensitive hybrid core-shell particles via in situ synthesis of gold nanoparticles using thermosensitive core-shell particles as a template. The template core-shell particles, with cores composed mainly of poly(glycidyl methacrylate) (GMA) and shells composed mainly of poly(N-isopropylacrylamide) (PNIPAM), were synthesized in aqueous medium, and functional groups such as thiol groups were incorporated into each particle. We found that these particles containing thiol group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(118 citation statements)
references
References 39 publications
1
114
3
Order By: Relevance
“…In the former case, gold metal ions are fi rst immobilized in the microgel network and subsequently reduced using a chemical agent such as NaBH 4 , which leads to the formation of gold nanoparticles only within the network pores, due to the localization of the AuCl 4 -in relatively higher concentrations within the network by complexation of the gold ions by amines [159] or thiols [160] . In the case of charged microgels, the electrostatic interactions between metal nanoparticles and the charged groups also facilitate the immobilization of metal nanoparticles inside the microgel particles [159] .…”
Section: Microgels/nanogels Network Composed Of Crosslinked Polymersmentioning
confidence: 99%
“…In the former case, gold metal ions are fi rst immobilized in the microgel network and subsequently reduced using a chemical agent such as NaBH 4 , which leads to the formation of gold nanoparticles only within the network pores, due to the localization of the AuCl 4 -in relatively higher concentrations within the network by complexation of the gold ions by amines [159] or thiols [160] . In the case of charged microgels, the electrostatic interactions between metal nanoparticles and the charged groups also facilitate the immobilization of metal nanoparticles inside the microgel particles [159] .…”
Section: Microgels/nanogels Network Composed Of Crosslinked Polymersmentioning
confidence: 99%
“…[14][15][16][17][18][19] A great number of possible applications have been discussed for these systems that include widely separate fields as, e.g., protein adsorption. 20,21 They have also been recently used as a template for the reduction of metal nanoparticles [22][23][24] for applications in catalysis. 23,24 A comprehensive review on the applications was given by Nayak and Lyon.…”
Section: Gelsmentioning
confidence: 99%
“…In many cases, microgels are composed of poly(N-isopropylacrylamide) (pNIPAm), which is a typical thermosensitive polymer with a lower critical solution temperature of around 31 1C. 5,6 PNIPAm-based microgels can be functionalized by constructing nanocomposites with inorganic nanoparticles [7][8][9][10] for application in more complex biotechnologies and nanotechnologies (for example, drug delivery, 11,12 chemical/biological separation 13,14 and photonic crystals [15][16][17][18] ). In addition, we reported that microgels can show selfoscillation, [19][20][21][22] coupled with the Belousov-Zhabotinsky (BZ) reaction, 23 which is an autonomous and periodic chemical reaction.…”
Section: Introductionmentioning
confidence: 99%